INDONESIAN-ENGLISH CODE MIXING: A CASE IN ONLINE LEARNING CLASS - Fatin Nadifa Tarigan; Juliana Juliana (Lexeme : Journal of Linguistics and Applied Linguistics, 2022)
English educators in all levels of education  in Indonesia nowadays strive through to make their college students master in speaking and writing English. One of the ways to succeed the students are by asking them  use English or Indonesian-English code-mixing in their classroom include in online learning class. This study aims at finding out the types of Indonesian-English code mixing in online learning class.  A descriptive qualitative method was used to perform this study. The data for this study employed the students’ chats in Google Meet and Whatsapp as platforms of online class. The subjects were English Education Department students of Universitas Pembinaan Masyarakat Indonesia in three online class. The   instrument   utilized was documentation. This study was conducted entirely online.  Therefore, the data were collected by screenshots of the chat then were categorized as code mixing and the types of code mixing. Content analysis was applied for analyzing the data.  The findings indicates that most of students used code mixing with types of word insertion with 52.4 %  continued by phrase insertion. The lowest percentage was types of idiom  insertion with 2.5%. Hence, the lecturer know what should be improved  for  the students. It is necessary to get used  to the students to use English idiom in order to improve their language skill.